PENGARUH KEWAJIBAN MORAL, KUALITAS PELAYANAN, PEMERIKSAAN PAJAK DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK BADAN - layata, sherly; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2014)
This study aims to determine the effect of moral obligation, quality of service, tax audits and tax penalties on taxpayer compliance in Service Tax Office South Badung. The number of samples taken at 100 corporate taxpayers registered in South Badung Service Tax Office with random sampling methods, especially the sampling area. Data was collected through interviews, questionnaires and documentation. The data analysis technique used is multiple linear regression analysis. Using the tools of SPSS 17 for windows. The results of this study are positively moral obligation, quality of service, tax audits and tax penalties affect taxpayer compliance in Service Tax Office South Badung.
Keywords: moral obligations, quality of services, tax audit, tax penalties, tax compliance